The structure, biosynthesis, and biological roles of fetuin-A: A review - Chekol Abebe, Endeshaw; Tilahun Muche, Zelalem; Behaile T/Mariam, Awigchew; Mengie Ayele, Teklie; Mekonnen Agidew, Melaku; Teshome Azezew, Muluken; Abebe Zewde, Edgeit; Asmamaw Dejenie, Tadesse; Asmamaw Mengstie, Misganaw (Frontiers in Cell and Developmental Biology, 2022)
Fetuin-A is a heterodimeric plasma glycoprotein containing an A-chain of 282 amino acids and a B-chain of 27 amino acid residues linked by a single inter-disulfide bond. It is predominantly expressed in embryonic cells and adult hepatocytes, and to a lesser extent in adipocytes and monocytes. Fetuin-A binds with a plethora of receptors and exhibits multifaceted physiological and pathological functions. It is involved in the regulation of calcium metabolism, osteogenesis, and the insulin signaling pathway. It also acts as an ectopic calcification inhibitor, protease inhibitor, inflammatory mediator, anti-inflammatory partner, atherogenic factor, and adipogenic factor, among other several moonlighting functions. Fetuin-A has also been demonstrated to play a crucial role in the pathogenesis of several disorders. This review mainly focuses on the structure, synthesis, and biological roles of fetuin-A. Information was gathered manually from various journals via electronic searches using PubMed, Google Scholar, HINARI, and Cochrane Library from inception to 2022. Studies written in English and cohort, case-control, cross-sectional, or experimental studies were considered in the review, otherwise excluded.